The Road to Bilingualism: Cases of Success - César Augusto García-Herreros Machado (Universidad de La Sabana, 2018)
This review presents an immersion model based on the ideas of Richard-Amato regarding task-based approach, and how it was adapted to Wiggin's Understanding by Design and 21st Century skills frameworks. This combination has nurtured and helped the immersion model to arise, where the content and language areas are responsible for the cognitive and communicative development in a learner. The institution recognizes itself as an alternative educational solution for its students, and periodically revises its policies to meet the needs that can emerge in their community. Thus, the immersion model applied in the institution has emerged as a flexible, yet well-grounded and solid program that aims to make the most of the content in different areas to help students develop their foreign language skills in English.